International law and conflict management in the Western Balkans: Impact on Bosnia, Albania, and Kosovo - Karaj, Stela; Xharo, Kristaq (International Journal of Innovative Research and Scientific Studies, 2025)
This paper examines the role of international law in conflict zones, focusing on the United Nations Security Council (UNSC) and its efforts to mitigate crises. By analyzing the Western Balkans conflicts—Bosnia (1995), Albania (1997), and Kosovo (1999)—the study highlights how international law serves as a stabilizing framework during periods of instability. It assesses key interventions, including the Dayton Agreement in Bosnia, Operation Alba in Albania, and the NATO-led intervention in Kosovo, showcasing both the strengths and limitations of UNSC mechanisms in addressing regional conflicts. This research evaluates the UNSC’s effectiveness in these crises, considering geopolitical rivalries, evolving concepts of sovereignty, and the complexities of humanitarian intervention. Drawing comparisons with contemporary conflicts in Ukraine and Gaza, the study extracts lessons from the Balkans to inform the UNSC’s approach to current and future crises. Through a historical and comparative analysis, it bridges theoretical perspectives with practical insights, offering recommendations for strengthening the UNSC’s application of international law. By examining the dynamic role of international law and multilateral institutions, the paper contributes to a deeper understanding of peace and security frameworks in conflict-prone regions, with a particular focus on the Western Balkans’ historical and geopolitical significance.